Steroid therapy still plays a crucial role and could serve as a bridge to the next promising treatments in patients with IgG4‐related sclerosing cholangitis: Results of a Japanese nationwide study. (25th May 2022) - Kubota, Kensuke; Kamisawa, Terumi; Nakazawa, Takahiro; Tanaka, Atsushi; Naitoh, Itaru; Takikawa, Hajime; Unno, Michiaki; Kawa, Shigeyuki; Masamune, Atsushi; Nakamura, Seiji; Okazaki, Kazuichi; ,
Abstract: Objective: The acceptable duration of steroid therapy for patients with IgG4‐sclerosing cholangitis (SC) has been under debate. Our aim is to clarify the feasible duration of steroid treatment. Design: We retrospectively reviewed the data of patients with IgG4‐SC and analyzed the following: biliary status during the steroid therapy, incidence of remission, relapse, relapse‐free survival rate, and steroid‐related complications (SRCs). Results: Remission was achieved in 99.5% (763/767) of patients who received steroid therapy, while the remission rate dropped to 63.6% (78/129) of patients who did not receive it. Relapse was noted in 19.7% (151/763) of the patients who received steroid. Besides, relapse rate went up 38.4% (30/78) of the counterpart. Normalization of the serum total bilirubin and serum alkaline phosphatase levels were achieved at 2 weeks regardless of biliary drainage. Multivariate analysis identified younger onset, MST less than 3 years, immunosuppressant, and steroid cessation as independent risk factors for relapse. Steroid‐free was achieved in the patients underwent MST only 3.4% over 54 months. SRCs were recorded in a total of 99 patients (12.9%) despite sufficient preemptive medications. Multivariate analysis identified history of malignancy and immunosuppressant as independent risk factors for SRCs. Conclusion: Steroid therapy should be continued for no <3 years to reduce the risk of relapse, with use of preemptive measures taken around 5 years. The biliary drainage might not be mandatory. Steroid as 1st line therapy could serve as a bridge to further promising treatments. Abstract : The acceptable duration of steroid therapy for IgG4‐sclerosing cholangitis remains debated. Kubota et al conclude that steroid therapy should be continued at least 3 years to reduce the risk of relapse, with preemptive measures taken around 5 years. Steroids as first‐line therapy could serve as a bridge to further promising treatments.